STRATEGI PEMASARAN PRODUKSI TAHU TEMPE DI LINGKUNGAN TAMAN SARI BULELENG - Kadek Duwik Ulantari (Arthaniti Studies, 2026)
The purposeof this study is to determine the implementation of marketing strategies used by tofu and tempeh producers in the Taman Sari area of Buleleng. This research employs a descriptive qualitative approach. The data collection techniques used in this study include observation and interviews. The observation activities involve recording events, observed objects, and other relevant aspects that support the ongoing research. Interviews were conducted with ten key informants to gather information regarding the implementation of marketing strategies used by tofu and tempeh producers. The data were analyzed through three stages: data reduction, data presentation, and conclusion drawing. The results of this study indicate that the marketing strategies applied in tofu and tempeh production significantly influence the level of demand and sales achieved by producers. The strategies used include improving product quality, setting competitive product prices, and continuously analyzing consumer demand in the market. Therefore, the implementation of marketing strategies in tofu and tempeh production in the Taman Sari area of Buleleng has enabled these production businesses to remain sustainable and competitive in the market until today